Advances in understanding the genetics of pig behaviour - Rydhmer, Lotta (Burleigh Dodds Series in Agricultural Science, 2021)
Breeding for behavioural traits may improve pig welfare and breeding for high production may decrease pig welfare. Maternal behaviours important for piglet production includes savaging, crushing and nursing. Behaviours of importance for production of pigs for slaughter includes feeding behaviour, tail biting and aggressive behaviour. These are complex traits and large amounts of data are needed for accurate genetic evaluation and selection.